Modulation of sea surface temperature in three oceans on precipitation increase over Northwest China during the past 60 years: A review - Ding, Yihui; Wu, Ping; Liu, Yanju (Frontiers in Climate, 2022)
Northwest China is a typical arid and semi-arid region that is part of Central Asia. However, during the past 60 years, the climate in Northwest China has shown a warm and humid trend, with both average and extreme precipitation continuing to increase. Humidification in Northwest China is mainly caused by anomalous westward water vapor transport. Change in the water vapor transport path is directly related to the Mongolian anticyclone anomaly and weakening of the Asian summer monsoon. Our research shows that interdecadal changes in sea surface temperature (SST) in the North Atlantic, North Pacific, and Indian oceans, play an important role in interdecadal adjustment of atmospheric circulation and the wetting climate over Northwest China. Since the 1980s, the Indian Ocean has been warming continuously, and the land–sea thermal gradient has weakened, resulting in a significant reduction in water vapor transport of the Asian summer monsoon. In contrast, anomalous northerly water vapor transport from the polar region increased. Concurrently, SST over the North Atlantic is also warming, and the Atlantic multidecadal oscillation (AMO) changes from the negative to positive phase, triggering anomalous anticyclones over Mongolia, which also leads to weakening of the Asian summer monsoon. Therefore, eastern China is affected by abnormal northeast winds. These northeast winds can continuously transport water vapor to the western region of China, leading to the prevalence of easterly winds in Northwest China. Moreover, Pacific decadal oscillation (PDO) changed from the positive to negative phase after the 1990s, which promoted the East Asian westerly jet to move to the Arctic and produce easterly anomalies in East Asia and Northwest China. Interdecadal changes in SST over the Indian, North Atlantic, and North Pacific Oceans all have reduced summer water vapor from the Indian Ocean. However, water vapor from the North Pacific and high latitudes (including the polar region) can be transported to Northwest China through easterly anomalies, resulting in increased precipitation and climate humidification.